Application of engineering through emotional (sensory) signals in the Library System UNMSM - Yenque Dedios, Julio (2014)
Theme based on sensory perception innovated relates to information technology and communication (ICT) details the use of a conventional system librarian and universal signaling in order to obtain optimum visual communication allowing timely identification research , location and orientation of the areas as information services to present an improvement of corporate identity, that is, the good image of the library as a safe and orderly organization. Having described the background and theoretical aspects of applicative model of library users with the SPSS statistical software test outlines, a program of signage being designed under the recommended safety standards for libraries. Complementing a set of symbols, signs and icons often used is appended.